Finance for a Greener future: Evolving the financial sector for ESG and sustainable corporate debt management - Bilal Haider Subhani; Shen Zunhuan; Muhammad Asif Khan (Borsa Istanbul Review)
This study investigates the impact of Environmental, Social, and Governance (ESG) investments on corporate debt financing (CDF) in the BRICS (Brazil, Russia, India, China, and South Africa) economies throughout 2010 to 2022. A central aspect of this research is the moderating role of financial sector development (FSD), which potentially influences how ESG commitments affect corporate financing strategies in these rapidly evolving markets. The findings of two-step system Generalized Method of Moment indicate a negative correlation between ESG investments and CDF, suggesting that increased ESG commitments may initially restrict access to debt financing. Nonetheless, FSD serves as an important moderating variable, converting this adverse effect into a favorable one. A strong financial sector offers substantial funds under relaxed terms. In line with Porter's win-win hypothesis, the results indicate that sustainable practices can strengthen competitive advantage and financial performance, highlighting the importance of advancing FSD and incorporating ESG factors into corporate finance.